2018
DOI: 10.1002/admi.201801610
|View full text |Cite
|
Sign up to set email alerts
|

Transflective Mesoscopic Nanoparticles Synthesized in the Leidenfrost Droplet as Black Absorbers

Abstract: Here, a new class of transflective oxide metaparticles that are able to capture solar radiation in a selective manner based on their size and morphology is demonstrated. The metaparticles possess an electronic polarization response “polarizonics” and show a specular reflective color at the visible frequencies. As a specific highlight, a resonating ultrathin reflective while transparent metacomposite, i.e., a transflective coating is designed. Further, a perfect solar absorber is devised whose function is morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It has been thought that the shiny and vivid colors are solely achievable by the optically symmetric and periodically structured materials, which is “not quite right,” based on our recent progresses in the field. Several disordered structures consisting of nanoparticles and molecules that are able to show coherent and cooperative specular reflection “polarizonic” responses have been recently introduced by us and implemented for creation of vivid colors. Despite various merits with respect to structural polarizonic coloration, this mode of specular reflected color is angular and polarization dependent thus inefficient for different applications such as optical measurement systems, colored display devices, and solar absorbers.…”
Section: Resultsmentioning
confidence: 99%
“…It has been thought that the shiny and vivid colors are solely achievable by the optically symmetric and periodically structured materials, which is “not quite right,” based on our recent progresses in the field. Several disordered structures consisting of nanoparticles and molecules that are able to show coherent and cooperative specular reflection “polarizonic” responses have been recently introduced by us and implemented for creation of vivid colors. Despite various merits with respect to structural polarizonic coloration, this mode of specular reflected color is angular and polarization dependent thus inefficient for different applications such as optical measurement systems, colored display devices, and solar absorbers.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the localized plasmon that is characterized by absorption and scattering of an oscillated dipole, which is an intrinsic property and does not consider the cooperative action of all matter (e.g., near‐field response, hotspot generation), polarizonics is an exceptional field that emerges from the cooperative and coherent interactions and interference of oscillating bounded dipoles of polarized materials. Elbahri's group has verified this hypothesis [ 31,36,37,39,40 ] both theoretically and experimentally and shown that a sheet of oscillated dipoles, “nanoparticles, atoms, or molecules,” behaves as a deterministic chaotic system that creates a macroscopic coherent response by the cooperative interference of the eigenvibrations. Thus, these random dipoles act as “artificial galaxies” with specular reflection in the Z direction, as observed on smooth conductor surfaces, but not yet reported for disordered ultrafine particles.…”
Section: Polarizonic Reflective Colorationmentioning
confidence: 99%
“…Recently, we challenged this general knowledge and provided a novel understanding by exploring polarizonic resonance with the specular reflectionbased colors of disordered plasmonic nanoclusters and nanocomposites, and artificial plasmonic molecules among other radiating dipoles. [31,[36][37][38][39][40] Indeed, the polarizonic colors emerging from such glassy and amorphous nanostructures could be of paramount technological importance for energy harvesting, biodetection, and aesthetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation